The Effect of Using Clustering Technique on Writing Achievement of the Eighth Grade Students of SMP Bala Keselamatan Kalawara - Cindy, Margaret; Munir, Syahrul; Budi, Budi; Rofiqoh, Rofiqoh (Journal of English Language and Education, 2026)
This research aims to determine whether the use of Clustering Technique can improve the writing achievement of class VIII students at SMP Bala Keselamatan Kalawara. This research used a quasi-experimental design by applying nonequivalent control group design. The population was class VIII students at SMP Bala Keselamatan Kalawara, consisting 37 students from two classes. The sample was class A as the experimental group and class B as the control group. Sample selection was carried out using saturated sampling. Tests were used to collect data consisting of pre-test and post-test. The tests result show that the average pre-test score obtained by the experimental group is 43.86, while the pre-test score obtained by the control group is 46.91. Then, the average post-test score for the experimental group is 69.00, while the control group is 54.94; the t-counted value (5.52) was higher than t-table value (1.690), which means that the hypothesis was accepted.